Capability of telecentre in developing rural community / Amirah Ab Halim and Marhaini Mohd Noor - Ab Halim, Amirah; Mohd Noor, Marhaini (2021)
Outbreak COVID-19 was declared as a pandemic on March 2020 by World Health Organization (WHO) (WHO, 2020). The outbreak of the virus has affected the economy and living style among the people in Malaysia (Shah et al., 2020). People around the world are affected by this pandemic situation and ought to live with new norms to prevent the spread of Covid-19. The government has imposed Movement Control Order (MCO) as part of initiatives to break the chain and curb transmission of the virus (Aziz et al., 2020). Practicing new norms in the community regardless of their income status and social status would be the necessity to break the chain of the pandemic and protect vulnerable groups (Lim et al., 2021). Hence, the pandemic situation has enforced society to make use of the technologies as a medium or tools in working operational, studies, communication, businesses, and social needs. However, obligatory to practice new norms among the society caused other issues for the left-behind community as low-level income households, special disabilities group and as well as for rural area community in terms of digital usage or information communication technology (ICT) usage.